(untitled) (Transport systems and technologies, 2023)
In this paper, we propose the solution of the scientific and applied problem of batch freight delivery in the intercity by road in terms of system’s limited resource of the system due to the development of long-distance freight delivery technology in terms of resource savings and the observation of the established level of reliability of the freight delivery functioning of the logistics system (FDLS). For certain parameters of cargo flow with limited resources of the transport market entities involved in the delivery process, the formation of a resource-saving delivery technology allows maximising the effect of the functioning of the system of delivery of consignment cargo by road in intercity traffic. To solve the problem, we used methods of mathematical modelling, a systematic approach, optimization methods (functions of many variables), the provisions of probability theory and mathematical statistics, methods of regression analysis. For the given operating conditions of the developed logistics system, the rational technology of long-distance batch freight delivery has been determined in terms of resource savings. It will reduce overall costs by 13.9% for the given level of the readiness of FDLS.